2007
DOI: 10.1590/s0101-81752007000400032
|View full text |Cite
|
Sign up to set email alerts
|

The influence of seasonality, tide and time of activities on the behavior of Sotalia guianensis (Van Bénéden) (Cetacea, Delphinidae) in Pernambuco, Brazil

Abstract: Data on Sotalia guianensis Van Bénéden, 1864 occurrence on the beaches of Pernambuco (Northeastern Brazil) is restricted to information on stranding and on printed material from local newspapers; actual observations of such animals have not been published. This study intends to determine the use of habitat, behavioral activities and assess the relationships between environmental factors and the recorded behavior. Observations were conducted on open sea coastal areas, on the beaches of Olinda and Piedade, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…The author suggests an opportunistic exploration of the direction and speed of the tide by estuarine dolphins to forage, enter and leave estuaries. Araújo et al (2007) found no significant differences between the relative frequencies of foraging events during flood and ebb tides in four port areas of Pernambuco. At Pontal Bay, the displacement direction of most individuals follows the tidal movement: an increased proportion of individuals move toward the back of the bay during the flood, and this proportion decreases during the ebb tide.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…The author suggests an opportunistic exploration of the direction and speed of the tide by estuarine dolphins to forage, enter and leave estuaries. Araújo et al (2007) found no significant differences between the relative frequencies of foraging events during flood and ebb tides in four port areas of Pernambuco. At Pontal Bay, the displacement direction of most individuals follows the tidal movement: an increased proportion of individuals move toward the back of the bay during the flood, and this proportion decreases during the ebb tide.…”
Section: Resultsmentioning
confidence: 64%
“…Hayes (1999) recorded a higher frequency of individuals in March at Iracema Beach in Ceará and related this abundance to heavy rainfall and the large amounts of fish present in the shallow waters of the area. In Pernambuco, Araújo et al (2007) observed a decrease in the number of individuals sighted with an increase in monthly precipitation. However, the frequency of sightings of estuarine dolphins was not related to precipitation intensity at Pontal Bay (Santos 2007).…”
Section: Discussionmentioning
confidence: 91%
“…Guiana dolphins seem to exhibit strong site fidelity, and tend not to move very far from population habitat areas (Wedekin et al 2007, Hardt et al 2010. In open coastal environments, Araújo et al (2007) found no significant effects of tidal cycles on area utilization or variation in behaviour of the Guiana dolphin, while Azevedo et al (2007) did find tidal effects in an estuarine environment.…”
Section: Introductionmentioning
confidence: 78%
“…Other studies evaluated sexual maturity by growth, measuring and weighing the gonads (Santos et al 2001, Rosas and Monteiro-Filho 2002, Da Silva et al 2007, Araújo et al 2007, Katsumata 2010, Perrin and Reilly 1984, Pomeroy 2011. However, studies reporting the microscopic anatomy of the female genital organs are scarce.…”
Section: Introductionmentioning
confidence: 99%